Multiple Herbicide–Resistant Junglerice (Echinochloa colona): Identification of Genes Potentially Involved in Resistance through Differential Gene Expression Analysis. Issue 3 (16th March 2018) - Wright, Alice A.; Rodriguez-Carres, Marianela; Sasidharan, Rajkumar; Koski, Liisa; Peterson, Daniel G.; Nandula, Vijay K.; Ray, Jeffery D.; Bond, Jason A.; Shaw, David R.
Abstract: Herbicide resistance, and in particular multiple-herbicide resistance, poses an ever-increasing threat to food security. A biotype of junglerice [ Echinochloa colona (L.) Link] with resistance to four herbicides, imazamox, fenoxaprop-P-ethyl, quinclorac, and propanil, each representing a different mechanism of action, was identified in Sunflower County, MS. Dose responses were performed on the resistant biotype and a biotype sensitive to all four herbicides to determine the level of resistance. Application of a cytochrome P450 inhibitor, malathion, with the herbicides imazamox and quinclorac resulted in increased susceptibility in the resistant biotype. Differential gene expression analysis of resistant and sensitive plants revealed that 170 transcripts were upregulated in resistant plants relative to sensitive plants and 160 transcripts were upregulated in sensitive plants. In addition, 507 transcripts were only expressed in resistant plants and 562 only in sensitive plants. A subset of these transcripts were investigated further using quantitative PCR (qPCR) to compare gene expression in resistant plants with expression in additional sensitive biotypes. The qPCR analysis identified two transcripts, a kinase and a glutathione S -transferase that were significantly upregulated in resistant plants compared with the sensitive plants. A third transcript, encoding an F-box protein, was downregulated in the resistant plants relative to the sensitive plants. As no cytochrome P450s were differentially expressed between the resistant and sensitive plants, a single-nucleotide polymorphism analysis was performed, revealing several nonsynonymous point mutations of interest. These candidate genes will require further study to elucidate the resistance mechanisms present in the resistant biotype.